2022
DOI: 10.3389/fphys.2022.1000944
|View full text |Cite
|
Sign up to set email alerts
|

Contact varroacidal efficacy of lithium citrate and its influence on viral loads, immune parameters and oxidative stress of honey bees in a field experiment

Abstract: With an almost global distribution, Varroa destuctor is the leading cause of weakening and loss of honey bee colonies. New substances are constantly being tested in order to find those that will exhibit high anti-Varroa efficacy at low doses/concentrations, without unwanted effects on bees. Lithium (Li) salts stood out as candidates based on previous research. The aims of this study were to evaluate Li citrate hydrate (Li-cit) for its contact efficacy against Varroa, but also the effect of Li-cit on honey bees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…At the end of the experiment on day 14, an increase in the activity of genes for GST and CAT confirmed that this microsporidium causes overexpression of oxidation-related genes [45]. In our previous study [46], in which the effect of lithium citrate was tested, the expression levels of genes for antioxidant enzymes depended on pathogen load. In contrast to the infected group (I), bees that were infected and supplemented (group IT) had lower gene transcript levels.…”
Section: Discussionsupporting
confidence: 59%
“…At the end of the experiment on day 14, an increase in the activity of genes for GST and CAT confirmed that this microsporidium causes overexpression of oxidation-related genes [45]. In our previous study [46], in which the effect of lithium citrate was tested, the expression levels of genes for antioxidant enzymes depended on pathogen load. In contrast to the infected group (I), bees that were infected and supplemented (group IT) had lower gene transcript levels.…”
Section: Discussionsupporting
confidence: 59%
“…The honey bee A. mellifera is thought to be the most negatively impacted by the honey bee mite V. destructor . The mite, which is present almost everywhere in the world, is the main factor contributing to the decline of honey bee colonies [ 78 ]. Due to its role as a mechanical or biological vector of pathogen microorganisms, notably viruses, with the potential to exacerbate pre-existing infections, and its feeding on the fat body and haemolymph of adult and growing honey bees, Varroa poses major health risks to its hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its role as a mechanical or biological vector of pathogen microorganisms, notably viruses, with the potential to exacerbate pre-existing infections, and its feeding on the fat body and haemolymph of adult and growing honey bees, Varroa poses major health risks to its hosts. [ 9 , 78 , 79 ]. With this in mind, acaricides, whether synthetic or natural-based, must be used continuously in order to control the mite infestation.…”
Section: Discussionmentioning
confidence: 99%
“…LiCl is an ideal compound under these circumstances, due to its high e cacy and good tolerability by adult bees (Stanimirovic et al 2021;Ziegelmann et al 2018). Some eld tests with lithium salts have already been performed, however most of them used a repeated dribbling method similar to the application of oxalic acid (Jovanovic et al 2022;Kolics et al 2020b;Kolics et al 2022).…”
Section: Introductionmentioning
confidence: 99%